THE FUNCTION OF INTERLEUKIN-6 IN PREDICTING COVID-19 SEVERITY: A CORRELATION STUDY BETWEEN GENE EXPRESSION AND PROTEIN CONCENTRATION - Ahmed Majeed Abdzaid; Ali Sabri Jabbar (European Science Publishing, 2024)
This study aimed to examine Interleukin-6 (IL-6) as predictive biomarker for COVID-19 severity, to achieve this aim, the protein concentration degree and gene expression was tested in 90 samples according to COVID-19 severity which had been classified as (Control, Mild, Moderate, and Severe COVID-19). The IL-6 gene expression was assessed by means of qPCR and the protein concentration changed into analyzed via ELIZA and Western Blot. The consequences revealed that, there was a positive correlation amongst IL-6 gene and protein levels to severity of COVID-19. Accordingly, the IL-6 play essential role as predictive biomarker for COVID-19 severity and play a pivotal function in COVID-19 prediction. Additional studies are wanted to verify these findings in larger cohorts and to analyze the precise mechanisms of IL-6 gene regulation across the various stages of COVID-19 infections
Keywords: COVID-19, IL-6, qPCR, gene expression, elisa, IL-6 concentration.